2018
DOI: 10.1111/pai.12841
|View full text |Cite
|
Sign up to set email alerts
|

Breastmilk cell trafficking induces microchimerism‐mediated immune system maturation in the infant

Abstract: Initiating breastfeeding within the first hour of life confers an important benefit in terms of child mortality and severe morbidity. Intestinal permeability to ingested macromolecules and immunoglobulins is limited to the first days of human life. These exchanges cease in the very early post-partum period but may increase beyond the neonatal period in response to local inflammation or introduction of a weaning food. This is an open access article under the terms of the Creative Commons Attribution-NonCommerci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
76
0
8

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(86 citation statements)
references
References 100 publications
2
76
0
8
Order By: Relevance
“…Maternal milk is not only a very rich source of nutrients indispensable for the infant (Dieterich, Felice, O'Sullivan, & Rasmussen, ) but also a functional food shaped by evolution (Alsaweed, Hartmann, Geddes, & Kakulas, ) with various bioactive compounds (Ballard & Morrow, ) like antimicrobial molecules (Ballard & Morrow, ), growth factors (Ballard & Morrow, ), casein fragments and lipids (Hill & Newburg, ), immune cells (Moles et al., ), antibodies (Ulfman, Leusen, Savelkoul, Warner, & van Neerven, ), and catalytically active antibodies (Nevinsky et al., ). It even contains maternal cells that integrate into the infant's gut walls creating localized microchimerism ensuring proper immunity development for the infant (Moles et al., ). Moreover, in mice, maternal milk stem cells were detected in the blood and the brain of the pups after sucking (Aydin, Yigit, Vatandaslar, Erdogan, & Ozturk, ).…”
Section: Micrornas In Milkmentioning
confidence: 99%
See 1 more Smart Citation
“…Maternal milk is not only a very rich source of nutrients indispensable for the infant (Dieterich, Felice, O'Sullivan, & Rasmussen, ) but also a functional food shaped by evolution (Alsaweed, Hartmann, Geddes, & Kakulas, ) with various bioactive compounds (Ballard & Morrow, ) like antimicrobial molecules (Ballard & Morrow, ), growth factors (Ballard & Morrow, ), casein fragments and lipids (Hill & Newburg, ), immune cells (Moles et al., ), antibodies (Ulfman, Leusen, Savelkoul, Warner, & van Neerven, ), and catalytically active antibodies (Nevinsky et al., ). It even contains maternal cells that integrate into the infant's gut walls creating localized microchimerism ensuring proper immunity development for the infant (Moles et al., ). Moreover, in mice, maternal milk stem cells were detected in the blood and the brain of the pups after sucking (Aydin, Yigit, Vatandaslar, Erdogan, & Ozturk, ).…”
Section: Micrornas In Milkmentioning
confidence: 99%
“…So far, the bulk of evidence supports milk microRNA bioaccessibility (survivability) in the human consumers, either adults or infants. In infants, the digestive tract is far less developed and exerts less harsh conditions (lower acidity and low enzymatic activity), allowing even immune cells and, other cells of milk, to survive and settle within the infant digestive tract wall (Cabinian et al., ; Moles et al., ). Moreover, infants are only fed with breast milk or milk formulations during the first 6 months of their existence.…”
Section: Milk Micrornas In Health and Diseasementioning
confidence: 99%
“…While the mature gut constitutes a remarkable defence system, the young infant gut remains vulnerable to infection during this dynamic period of intestinal adaptation. For example, the newborn has increased intestinal permeability for several weeks after birth to enable the process of maternal micro--chimerism 11 , which might facilitate passage of cell-associated viruses in breast milk; there is relative achlorhydria in the stomach, which impairs neutralisation of viruses 15 ; and infants have a large population of intestinal CCR5+ memory CD4+ T--cells, which provide a highly susceptible pool of target cells for HIV 16 . Furthermore, exposure to viruses in early life occurs at a time when anti--viral immunity is not well developed due to enhanced tolerogenic responses, reduced Th1 development, and naïve lymphocyte predominance; the capacity to control viral infections only matures over the first few years 17 .…”
Section: Introductionmentioning
confidence: 99%
“…However, little attention has been devoted to characterize key genes involved in milk secretion in mammals. In humans, increasing evidence has demonstrated that breastfeeding is highly beneficial for infants, including reduction in the incidence of diarrhea and pneumonia 3,4 , decreased risk of obesity 5 , and increased immune system maturation 6 . Moreover, breastfeeding can protect mothers against cardiovascular disease, metabolic syndrome 7 , and breast cancer 3 .…”
mentioning
confidence: 99%